The Effect Of The Implementation Of E-Samsat And Tax Sanctions On The Level Of Compliance Of Motor Vehicle Taxpayers In The Regional Revenue Agency Of North Sulawesi Province In 2019-2021 - TURAMBI, Florensia; SONDAKH, Jullie J.; BUDIARSO, Novi S. (PT Keberlanjutan Strategis Indonesia, 2022)
Tax accounting is a matter of being able to determine the amount of tax owed based on a financial statement prepared by the company. In general, tax accounting is an accounting that is set for a purpose in order to obtain a determination of the amount of tax owed. Sistem Administrasi Manunggal Satu Atap (SAMSAT). E-samsat is a breakthrough from related parties to make it easier for taxpayers to carry out their obligations to pay motor vehicle taxes in their jurisdiction. Tax sanctions are a guarantee that the provisions of tax laws and regulations (tax norms) will be followed/obeyed/obeyed (Mardiasmo, 2019:72). This study has the aim of determining the effect of the application of E-samsat and tax sanctions on the level of compliance of motor vehicle taxpayers at the Regional Revenue Agency of North Sulawesi Province. The type of research used in this study is correlation quantitative research. The number of samples used was 100 respondents using the purposive sampling method collected through a questionnaire (google form). This study uses data analysis techniques, namely multiple linear regression analysis. The results of this study show that the application of E-samsat does not affect the level of compliance of motor vehicle taxpayers, while tax sanctions have a positive effect on the level of compliance of motor vehicle taxpayers at the Regional Revenue Agency of North Sulawesi Province.